Learning Al-Qur’an Signs as An Effort to Instill Religious Character for Learners with Hearing Disabilities at SLB-B YPPALB Magelang City - Wijaya, Kemal Pasha; Nasywa, Nabiel Aufa Failasufian; Maulidia, Sofia (Proceeding International Conference on Religion, Science and Education, 2025)
The development of science and technology in the globalization era presents various challenges that necessitate the cultivation of religious character among student throughout the educational process. As a fundamental right, Islamic religious education holds a significant position in instilling this character in all individuals, including deaf student. Legally, the right to education is guaranteed by Law Number 08 of 2016 concerning people with disabilities. However, the data of the Central Bureau of Statistics in 2022 revealed that only 4.31% of people with disabilities had access to education. Furthermore, the National socio-economic data from 2023 indicates that there were 22.97 million people with disabilities, with 2.46% were individuals with Deaf disabilities. This disparity in educational access is rooted in accessibility discrimination across various aspects of life. The Ministry of Religious Affairs, through the Lajnah Pentashihan Al-Quran, introduced Al-Qur’an sign guidelines to help fulfill the religious rights of individuals with Deaf disabilities. Within the educational framework, the Al-Qur’an sign is an approach in providing religious instruction and rights for deaf student. This study aims to describe the instruction of the Al-Qur’an sign as a means of fostering religiosity in deaf student at SLB-B YPPALB in Magelang City. A qualitative research method was used, with data collection techniques involving observations and interviews. The sources of data involved in the planning and implementation of the Al-Qur’an sign learning program: The principal, Islamic Religious Education teachers, and deaf student. Once data saturation was achieved, data reduction was conducted as a form of analysis. The results indicated that deaf student were able to read the Qur’an using both verbal expressions and hand gestures, effectively instilling religious character across various dimensions of their lives.